Topical Review: An Update of Diagnostic and Management Algorithms for Acquired Blepharoptosis. Issue 3 (March 2022) - Nichols, Kelly K.; Malloy, Kelly A.; Karpecki, Paul M.; Bacharach, Jason; Douglas, Raymond S.; Foster, Shane; Gromacki, Susan J.; Whitley, Walter O.
Abstract : SIGNIFICANCE: Acquired ptosis is a condition of the upper eyelid that has negative cosmetic and functional effects but is likely underdiagnosed and undertreated. Given the evolving understanding of the condition and expanding therapeutic options, this review reappraised published evidence and clinical experience regarding diagnosis and treatment of acquired ptosis. The authors met over two structured virtual working sessions to review current evidence and develop timely recommendations for acquired ptosis identification, differential diagnosis, characterization, and treatment selection. Diagnostic algorithms, plus management and referral guidelines, are presented. Eyelid evaluation and, when needed, ptosis diagnostic workup are essential in the comprehensive eye examination. Acquired ptosis can be efficiently identified via patient questionnaire, history, and photograph review combined with assessment of eyelid position and symmetry using established methods. When ptosis is present, it is essential to evaluate onset, symptoms, pupil diameter, and extraocular muscle function to identify or rule out serious underlying conditions. If signs of serious underlying etiology are present, immediate referral/follow-up testing is required. After ruling out serious underlying causes, masquerade conditions, and pseudoptosis, pharmacologic or surgical treatment should be selected based on the clinical evidence. Effectively managing acquired ptosis requires practice-wide commitment to thorough eyelid evaluation, accurate diagnosis, and adoption of new treatment modalities. Aided by evolving pharmacologic therapeutic options, shifting from a "detect and refer" to a "diagnose and manage" approach can support identification and treatment of more patients with acquired ptosis, particularly mild-to-moderate cases.